Management of Status Epilepticus - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
The care given to 8 children with epilepsy admitted with convulsive status epilepticus during 1990 is evaluated at the University Hospital of Wales, Cardiff.